1982
DOI: 10.1530/acta.0.0990326
|View full text |Cite
|
Sign up to set email alerts
|

Plasma gonadotrophins profile in relation to body composition in underprivileged boys

Abstract: The plasma concentrations of follicle-stimulating hormone (FSH) and luteinizing hormone (LH) were measured in 250 underprivileged boys (UP boys) aged 9.0 to 15.9 years living in a State orphanage and in 357 clinically healthy boys of the same age (with weight and height between the 3rd and 97th percentile for Mexican standards) and correlated with chronological age (CA), weight, height and calculated lean body mass (LBM) and total body fat (TBF). On a group basis, UP boys had a 2 years delay in the onset of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
1984
1984

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In black SA boys versus white boys, in this study high LH levels are associated with low DHEA and androstenedione levels. Interestingly, Parra et al (58) reported higher plasma levels of LH in underpriviledged Mexican boys up to 13 years of age who concomitantly had a two year delay in puberty when compared with 'well to do' Mexican boys. Thus in less socioeconomically advanced societies late maturation in children may be associated not only with an altered CNS-hypothalamic maturation but also delayed adrenal stimulation.…”
Section: Age In 'Cmmentioning
confidence: 99%
“…In black SA boys versus white boys, in this study high LH levels are associated with low DHEA and androstenedione levels. Interestingly, Parra et al (58) reported higher plasma levels of LH in underpriviledged Mexican boys up to 13 years of age who concomitantly had a two year delay in puberty when compared with 'well to do' Mexican boys. Thus in less socioeconomically advanced societies late maturation in children may be associated not only with an altered CNS-hypothalamic maturation but also delayed adrenal stimulation.…”
Section: Age In 'Cmmentioning
confidence: 99%